Enriching creative communities through Young Adult (YA) literature: a content analysis of zines from Philippine High School for the Arts - Veloso, Reya Mari Soriaga (ASEAN Journal of Community Engagement, 2020)
Prompted by the recent boom of zine-making and the active participation of youth in the local art scene, this paper is focused on determining the role of zines in the lives, culture of creation, and community engagement of young adults (YAs) and creating a typology based on the coming-of-age themes presented in fiction and nonfiction zines created by students at Philippine High School for the Arts (PHSA). To do so, the researcher collected zines from various events and expos, chose zines written by YAs (PHSA students in particular), conducted focus-group and individual interviews among the authors, and performed content analysis on all the materials collected. The results indicate that zines are used for self-expression, community building, and self-publishing. Moreover, themes such as permanence versus transience, relationship-building, nostalgia, language as a shaper of identity, and acts of subversion are common among coming-of-age narratives. Finally, this study was able to conclude that YA zines are a form of counter-storytelling, provide an alternative creative community to the youth, and act as a means for sociological theorizing, all of which are necessary functions for enriching creative communities among the youth.